2018
DOI: 10.1093/mnras/sty2946
|View full text |Cite
|
Sign up to set email alerts
|

Observational diagnostics of elongated planet-induced vortices with realistic planet formation time-scales

Abstract: Gap-opening planets can generate dust-trapping vortices that may explain some of the latest discoveries of high-contrast crescent-shaped dust asymmetries in transition discs. While planet-induced vortices were previously thought to have concentrated shapes, recent computational work has shown that these features naturally become much more elongated in the gas when simulations account for the relatively long timescale over which planets accrete their mass. In this work, we conduct two-fluid hydrodynamical simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 58 publications
5
30
1
Order By: Relevance
“…The disc also contains two bright spiral arms extending out to ≈ 75AU. This disc is also particularly interesting as it is currently the only observational result we have that shows the features identified by Hammer et al (2019), pertaining to an elongated vortex forming as a result of a planet growing in the disc. Fung & Dong (2015); Dong & Fung (2017); Cazzoletti et al (2018) show that these phenomena could possibly be explained by a planet of 5.0MJ (q = 5.0 × 10 −3 ) situated between the bright ring and the asymmetry.…”
Section: Hd135344bmentioning
confidence: 88%
See 1 more Smart Citation
“…The disc also contains two bright spiral arms extending out to ≈ 75AU. This disc is also particularly interesting as it is currently the only observational result we have that shows the features identified by Hammer et al (2019), pertaining to an elongated vortex forming as a result of a planet growing in the disc. Fung & Dong (2015); Dong & Fung (2017); Cazzoletti et al (2018) show that these phenomena could possibly be explained by a planet of 5.0MJ (q = 5.0 × 10 −3 ) situated between the bright ring and the asymmetry.…”
Section: Hd135344bmentioning
confidence: 88%
“…Additionally, recent investigation into the shape of planet induced vortices have accounted for the timescale over which the planet grows and have found that vortices can become elongated (Hammer et al 2017). As a result elongated vortices have their own specific observational features (Hammer et al 2019) that have potentially been observed (Pérez et al 2014;Cazzoletti et al 2018). However, the majority of observational results do not show the features that imply elongated vortices, although this may be due to the resolution of the observations In this paper we are investigating the required planet growth timescales for which no vortices are formed in a protoplanetary disc.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the presence of the companion, not present in the previous simulations, plays an important role in the location of the large dust grains. Hammer et al (2019Hammer et al ( , 2021 found that a large vortex characterized by a flat pressure bump would be sensitive to the overlapping of spiral density waves. Dust grains will then not concentrate in a small and centered area but in an elongated and complex structure, with a possible off-centered peak, a skewness around this peak, or even a double-peaked structure.…”
Section: Observations and Theories Regarding The Possible Existence Of A Large Vortex Around Hd 142527mentioning
confidence: 99%
“…This study was focused on explaining as many features as possible with the excitation provided by the eccentric stellar companion. However, it must be noted than SPH solvers generate numerical viscosities ∼10 −2 (Arena & Gonzalez 2013), which are much greater than typical values used in RWI vortex studies 3 (Lyra et al 2009;Hammer et al 2017Hammer et al , 2019Ono et al 2016), so this possibility was inherently not included in their study. In Fig.…”
Section: Origin Of the Cavity In Hd 142527mentioning
confidence: 99%